Somerset Maugham’s rare tribute to the womankind - Sai, B. Sudha; Kumari, Y.Kusuma (International Journal of Psychosocial Rehabilitation, 2020)
William Somerset Maugham, one of the famous English short story writers of twentieth century, is known to present his women characters as bloody, immature, imbalanced and loud in most of his short stories. The present article on the other hand is about his best homage to the womankind through the short story “The Colonel’s Lady”. It is one of the finest short-stories ever written by Somerset Maugham, in its length, characterization, matter, theme, situations and settings to give the public what they want. An excellent thing in this outstanding piece of craftsmanship is the character of the Colonel’s wife. His professionalism makes one marvel at its details, composition and ability to touch one’s soul with feelings of compassion for the Colonel’s lady. Every sentence, paragraph, fragment and everything in the story sit as a perfect gem in an exquisite design and the other characters leap off the page to become breathing creatures. Even if one is not a fan of the short story form, after reading this story feels that Maugham’s writing is an exception.